Carbon Profiles of Mongolian Dwellings: Ger vs. Baishin - Uelun-Ujin Purev (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This study evaluates the carbon footprints of two traditional Mongolian dwellings—the portable Ger and the self-built Baishin—through a comprehensive life cycle assessment (LCA). The Ger, prevalent among nomadic communities, relies on wood and coal-fired stoves for heating, leading to high operational emissions despite its minimal embodied carbon. Conversely, the Baishin, a permanent structure constructed from timber, bricks, or concrete, incurs higher embodied emissions but can achieve reduced operational emissions with effective insulation. Utilising OpenLCA and the Ecoinvent v3.11 database, the analysis spans material extraction, construction, operational energy use, and end-of-life disposal under typical Mongolian conditions. Results highlight the Ger’s lower cumulative energy demand (880,446,708 MJEq) and ecological footprint (59,409 m²a) compared to the Baishin’s higher impacts (934,217,037 MJEq and 279,801,890 m²a). These findings underscore the potential for energy-efficient retrofitting and sustainable material choices to mitigate emissions. The study provides actionable insights for developing low-carbon housing strategies tailored to Mongolia’s cold climate, contributing to climate change mitigation while preserving cultural heritage.